Budidaya Ternak Cacing Tanah (Lumbricus Rubellus) Sebagai Implementasi System Zero Waste di Lingkungan Peternak Ruminansia Desa Bagorejo Jember - Gayuh Syaikhullah; M Adhyatma; Satria Budi Kusuma (J-Dinamika : Jurnal Pengabdian Masyarakat, 2021)
Ruminant livestock groups in Jember Regency, especially in Bagorejo Village, have several problems that need to be resolved. A large livestock population makes breeders need a solution related to livestock waste, currently not being fully utilized. Several breeders have tried to use livestock waste as biogas and organic fertilizer. However, biogas' efficiency is still at a minimum level, and organic fertilizers' production is deemed less profitable from breeders' perspective. Ruminant breeders in Bagorejo Village expect a solution to utilizing their livestock waste which can be converted into a good side business. The community service team from the Jember State Polytechnic Animal Husbandry Department came with the results of research related to the use of Azotobacter sp bacteria in utilizing livestock waste. The utilization of these bacteria can convert livestock waste into optimal media for earthworms (Lumbricus rubellus). In the process of dissemination to farmers in Bagorejo village, the results were satisfactory. In addition to training and education, we also conduct mini-research in the breeder environment to convince farmers that the optimization of earthworm livestock can be helped by using the bacterial culture of Azotobacter sp. In this mini-research, we made three treatments for earthworm media, (P1) media without any addition, (P2) media with the addition of Azotobacter sp culture, and (P3) media with the addition of EM4. Each medium is sown with 500 grams of worm seeds. After that, maintenance is carried out for four weeks, and the final results of raising the earthworms are weighed. After weighing, P1 gets a final weight of 1.3kg, P2 receives a final weight of 2.4kg, and P3 gets a final weight of 1.8kg. From the results of the mini-research conducted by the team and breeders, the hope is that it will provide solutions to farmers that the use of livestock waste can be a medium for worm livestock. And with the addition of Azotobacter sp culture, it can make raising earthworms more optimal and can be a sustainable and profitable side business.